Selected Enzyme Inhibitory Effects of Euphorbia characias Extracts. (29th May 2018) - Fais, Antonella; Era, Benedetta; Di Petrillo, Amalia; Floris, Sonia; Piano, Dario; Montoro, Paola; Tuberoso, Carlo Ignazio Giovanni; Medda, Rosaria; Pintus, Francesca
Abstract : Extracts of aerial part of Euphorbia characias were examined to check potential inhibitors for three selected enzymes involved in several metabolic disorders. Water and ethanol extracts from leaves and flowers showed in vitro inhibitory activity toward α -amylase, α -glucosidase, and xanthine oxidase. IC50 values were calculated for all the extracts and the ethanolic extracts were found to exert the best effect. In particular, for the α -glucosidase activity, the extracts resulted to be 100-fold more active than the standard inhibitor. The inhibition mode was investigated by Lineweaver-Burk plot analysis. E. characias extracts display different inhibition behaviors toward the three enzymes acting as uncompetitive, noncompetitive, and mixed-type inhibitors. Moreover, ethanolic extracts of E. characias showed no cytotoxic activity and exhibited antioxidant capacity in a cellular model. The LC-DAD metabolic profile was also performed and it showed that leaves and flowers extracts contain high levels of quercetin derivatives. The results suggest that E. characias could be a promising source of natural inhibitors of the enzymes involved in carbohydrate uptake disorders and oxidative stress.